Who was Genghis khan - Medina nico; Medina nico (New York Penguin Workshop, 2014)
Named Temujin at birth by his nomadic family in early Mongolia, the great Genghis Khan used his skill and cunning to create the Mongol Empire and conquer almost the entire continent of Asia. As ruler of the largest empire in human history, he was as respected as he was feared. Learn more about the man and the legend in Who Was Genghis Khan?